Physical And Non-Physical Work Environment On Employee Performance - Josephus Noya (Cita Konsultindo Research Center, 2024)
This study aims to examine the impact of both physical and non-physical work environments on employee performance. Employing a descriptive-quantitative approach with a causal correlation design, the research was conducted at the Department of Housing and Settlement Areas in Buru Regency over a period of two months. The study population comprised all employees of the Buru Regency Housing and Settlement Area Service, totaling 105 individuals, including 35 civil servants and 60 honorary workers. Employing a full sampling method, data were analyzed using multiple linear regression analysis. The findings show that partially and simultaneously, the physical and non-physical work environment has a positive and significant effect on employee performance at the Housing and Settlement Area Office of Buru Regency.